PELUANG DAN TANTANGAN PENGEMBANGAN SAYUR HIDROPONIK DALAM KEWIRAUSAHAAN DI KELURAHAN LOLU UTARA KECAMATAN PALU TIMUR - Moh Sadewa Ladder; Putri Amelia H; Sucianti Mangando; Widy Widy; Nuraisyah Nuraisyah; Gita Farista (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Currently, advances in information technology have developed rapidly, one of which is automatic tools to help farmers in urban areas who have limited land. Almost all residents in cities always have the problem of limited land due to dense population, therefore using information to help their work, agricultural cultivation technology with a hydroponic system has been made an alternative for people who have limited land or yards, so that it can be used as a source of income. adequate. Hydroponics has a loose meaning, namely the technique of farming using water as a medium (Dewantoro, 2012), with an emphasis on fulfilling the nutritional needs of plants, or in the everyday sense of farming without soil. The hydroponic planting technique was initiated by the increasing attention of humans. about the importance of the need for fertilizer for plants. The growth of a plant can still develop well if the nutrients needed are always sufficient.